Sacred Ecology Unleashed: How Islamic Jurisprudence is Reshaping Environmental Education in Southeast Asia - Dian Wildan; Basuki Basuki; Arif Rahman Hakim; Fahad Abdusomad; Uus Ruswandi (Yayasan Letiges Konsultan Sosial, 2025)
This study addresses the gap in systematic frameworks connecting Islamic environmental jurisprudence with contemporary environmental education principles, analyzing current practices and developing evidence-based integration models. This study employed a systematic literature review with a mixed-method synthesis following PRISMA guidelines. Data consisted of 53 peer-reviewed empirical articles published between 2021–2025, retrieved from the Scopus database using structured keyword combinations related to Islamic education and environmental sustainability. Data were collected through systematic screening, inclusion–exclusion criteria, and standardized extraction forms. Analysis was conducted using directed and conventional content analysis combined with thematic synthesis to identify integration patterns, challenges, and opportunities. Trustworthiness was ensured through triangulation of sources, transparent audit trails, and expert validation to enhance reliability and analytical rigor. The results show uneven integration of environmental education in Islamic boarding schools (pesantren). Most institutions remain at early stages, with 53% applying thematic integration that embeds environmental issues superficially within Islamic subjects, while 23% offer specialized courses and only 9% achieve comprehensive institutional integration aligned with Islamic ecological principles such as khalifah fi al-ardh and maqashid al-shari‘ah. The remaining 15% reflect sporadic inclusion with minimal educational impact. These patterns indicate limited systemic transformation within Islamic education. Major constraints include teacher competency gaps, resource limitations, and weak policy support, while opportunities arise from increasing sustainability policies, digital learning potential, and support from Islamic organizations, positioning pesantren as strategic actors for advancing integrated Islamic environmental education.